5-Bis-(2,6-difluoro-benzylidene) Cyclopentanone Acts as a Selective 11β-Hydroxysteroid Dehydrogenase one Inhibitor to Treat Diet-Induced Nonalcoholic Fatty Liver Disease in Mice - Guan, Hongguo; Wang, Yiyan; Li, Huitao; Zhu, Qiqi; Li, Xiaoheng; Liang, Guang; Ge, Ren-Shan (Frontiers in Pharmacology, 2021)
Background: 11β-Hydroxysteroid dehydrogenase one is responsible for activating inert glucocorticoid cortisone into biologically active cortisol in humans and may be a novel target for the treatment of nonalcoholic fatty liver disease. Methods: A series of benzylidene cyclopentanone derivatives were synthesized, and the selective inhibitory effects on rat, mouse and human 11β-hydroxysteroid dehydrogenase one and two were screened. The most potent compound [5-bis-(2,6-difluoro-benzylidene)-cyclopentanone] (WZS08), was used to treat nonalcoholic fatty liver disease in mice fed a high-fat-diet for 100 days. Results: WZS08 was the most potent inhibitor of rat, mouse, and human 11β-hydroxysteroid dehydrogenase 1, with half maximum inhibitory concentrations of 378.0, 244.1, and 621.1 nM, respectively, and it did not affect 11β-hydroxysteroid dehydrogenase two at 100 μM. When mice were fed WZS08 (1, 2, and 4 mg/kg) for 100 days, WZS08 significantly lowered the serum insulin levels and insulin index at 4 mg/kg. WZS08 significantly reduced the levels of serum triglycerides, cholesterol, low-density lipoprotein, and hepatic fat ratio at low concentration of 1 mg/kg. It down-regulated Plin2 expression and up-regulated Fabp4 expression at low concentration of 1 mg/kg. It significantly improved the morphology of the non-alcoholic fatty liver. Conclusion: WZS08 selectively inhibits rat, mouse, and human 11β-hydroxysteroid dehydrogenase 1, and can treat non-alcoholic fatty liver disease in a mouse model.